A fluorescent light-up probe based on AIE and ESIPT processes for β-galactosidase activity detection and visualization in living cells. Issue 47 (9th November 2015) - Peng, Lu; Gao, Meng; Cai, Xiaolei; Zhang, Ruoyu; Li, Kai; Feng, Guangxue; Tong, Aijun; Liu, Bin
Abstract : A fluorescent probe with both AIE and ESIPT characteristics is developed for a β-galactosidase activity study in solution and living cells. Abstract : A novel fluorescent probeSA-βGal is reported here with light-up response to β-galactosidase.SA-βGal possesses the β-galactopyranoside group to react with β-galactosidase and releases the fluorescent salicylaldehyde azine with both aggregation induced emission (AIE) and excited-state intramolecular proton transfer (ESIPT) characteristics. The linear fluorescent response enables the in vitro quantification of β-galactosidase activity in a range of 0–0.1 U mL −1 with a detection limit of 0.014 U mL −1 . The probe exhibits significant advantages, such as no self-quenching at high concentrations, a large Stokes shift (190 nm) and high specificity to β-galactosidase with an excellent light-up ratio of 820 fold. Moreover, thanks to its good retention in living cells, the application ofSA-βGal for the imaging of cellular β-galactosidase was also achieved with high contrast.